(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess left ventricular function, including global longitudinal strain measured by two-dimensional speckle tracking echocardiography, before and after percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction presenting late after 48 hours. Methods: A prospective longitudinal study with a before-after design was conducted in 40 patients with late-presenting ST-segment elevation myocardial infarction at Vietnam National Heart Institute. All patients underwent percutaneous coronary intervention. Left ventricular ejection fraction and average global longitudinal strain (GLS Avg) were measured before intervention and at 30 days. Multivariable linear regression was used to identify independent predictors of longitudinal strain recovery. Results: Compared with baseline, mean left ventricular ejection fraction improved from 49.44 ± 10.26% to 53.28 ± 11.35%, and GLS Avg improved from -11.86 ± 4.61% to -13.37 ± 3.91%. In multivariable analysis, only baseline GLS Avg (B = -2.8; p = 0.009) and a left anterior descending artery culprit lesion (B = -2.37; p = 0.024) were independent predictors of longitudinal strain recovery. Conclusion: Percutaneous coronary intervention in patients with late-presenting acute myocardial infarction produced a marked improvement in systolic function and left ventricular longitudinal strain at 30 days. Baseline left ventricular global longitudinal strain and an left anterior descending culprit lesion were independent predictors of the magnitude of longitudinal strain recovery, outperforming traditional indices such as baseline left ventricular ejection fraction or NT-proBNP.